2010
DOI: 10.1159/000319472
|View full text |Cite
|
Sign up to set email alerts
|

A History of Prior Bare Metal Stent Restenosis Is Associated with Major Adverse Cardiac Events in Subsequent Bare Metal Stenting of de novo Coronary Lesions

Abstract: Objective: To investigate the risk of major adverse cardiac events (MACE) in patients with a history of bare metal stent (BMS) restenosis who undergo subsequent bare metal stenting of a geographically distinct, de novo coronary lesion. Methods: We conducted a retrospective review of 72 BMS procedures performed in geographically distinct, de novo coronary lesions in patients with a history of previous BMS placement at least 3 months prior to the second, index stent procedure. Patients with a history of in-stent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Yet, these conclusions may be helpful to interventional cardiologists who are daily discussing and debating what the optimal intra-coronary device for the individual patient is: DES or BMS? The findings of Ferguson et al [1] are supported by those of previous studies that reported higher rates of restenosis in patients with a previous history of restenosis in a different coronary location [2,3] , or one may say 'restenosers'. However, the present report is the first to deal solely with repeated BMS restenosis.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Yet, these conclusions may be helpful to interventional cardiologists who are daily discussing and debating what the optimal intra-coronary device for the individual patient is: DES or BMS? The findings of Ferguson et al [1] are supported by those of previous studies that reported higher rates of restenosis in patients with a previous history of restenosis in a different coronary location [2,3] , or one may say 'restenosers'. However, the present report is the first to deal solely with repeated BMS restenosis.…”
supporting
confidence: 65%
“…The findings of the study by Ferguson et al [1] are of clinical importance to the daily decision-making in the catheterization laboratory. They provide us with a solid clinical parameter to detect patients that would benefit from DES rather than BMS.…”
Section: Meir Arielmentioning
confidence: 90%
See 1 more Smart Citation
“…Initially the bare-metal stent (BMS) reduced the rate of restenosis. However, the BMS was associated with a high rate of in-stent restenosis that usually developed within 3–12 months of initial stent implantation [Ferguson et al 2010]. Previously published randomized controlled trials have shown lower rates of clinical and angiographic restenosis and major adverse cardiac events with the drug-eluting stent (DES) [Indolfi et al 2005; Tanabe et al 2003; Colombo et al 2003; Ong et al 2005; Morice et al 2002; Hermiller et al 2005; Bavry et al 2005].…”
Section: Introductionmentioning
confidence: 99%